PENGARUH PENERAPAN TEKNIK PEMBELAJARAN TRI FOKUS STEVE SNYDER TERHADAP PENINGKATAN KEMAMPUAN MEMBACA EFEKTIF - Rizca Maya Sari (Universitas Negeri Medan, 2015)
This study aimed to determine the effect of learning techniques Tri Focus SteveSnyder to improved reading skills effectively. The population in this research were 260students of class X SMA Negeri 1 Talawi Coal District. The sample in this studyamounted to 43 people were taken to probaliti techniques. The instruments used to collectthe data is an essay test. The method used in this study is a quasi-experimental or quasiexperiment. Of processing the data obtained with the pre test mean = 63.13, standarddeviation = 7.23. The results of the post-test mean = 81.04, standard deviation = 7.43,then didapatlah t0 at 11.26. Furthermore t0 is known, then consulted with ttabel at 5%significance level with df = n-1 = 43-1 = 42. df = 42 obtained from the level ofsignificance of 5% = 2.02. Because t0 obtained greater than ttable ie 19.88> 2.02, thenull hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.Concluded that there is a significant influence on the use of learning techniques TriFocus Steve Snyder to improved reading skills effectively 2nd semester class X SMANegeri 1 Talawi District Coal learning year 2009/2010.